Pengaruh Penerapan Green Investment dan CSR Terhadap Profitabilitas pada Perusahaan Mining Coal and Lignite di Bursa Efek Indonesia - Ummy Apriliantika; Risal Risal; Renny Wulandari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted to determine the extent of the influence of green investment and corporate social responsibility (CSR) on profitability in coal and lignite mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. A total of 19 companies were selected as samples in this study. This study used a quantitative approach with multiple linear regression analysis. The data sources in this study were annual reports and sustainability reports published by companies over a five-year period. The results of the study showed that coal and lignite mining companies have consistently adopted green investment, such as environmental costs and CSR implementation, in their financial reports. Based on this study, it is evident that the implementation of green investment and CSR has a positive and significant effect on the profitability of coal and lignite mining companies on the Indonesia Stock Exchange. These findings reinforce that the implementation of green investment and CSR is not only a sustainability obligation, but also a strategy that supports increased company profitability, thus providing a basis for further research to gain a deeper understanding of the mechanism that links green investment and CSR with company profitability.